USE OF BLENDED FIBER YARNS IN THE WEFT OF SHIRTING FABRICS AND THEIR COMPREHENSIVE ASSESSMENT (Web of Technology: Multidimensional Research Journal, 2025)
This article highlights the importance of using various blended fiber yarns in the production of shirting fabrics. Various methods for assessing the quality indicators of shirting fabrics are presented. A comprehensive assessment method was used to determine the impact on the quality indicators of shirting fabrics woven from blended fiber yarns. For the comprehensive assessment, experimental fabric samples were woven in 5 variants based on plain weave with a weft density of 10 cm being 225, using yarn samples spun from a cotton/polyester 70/30 fiber blend and 100% cotton yarn in the weft. Several indicators of the fabric samples were determined, such as air permeability, hygroscopicity, electrostaticity, color fastness, breaking strength, change in dimensions after wet processing, and fabric composition, and the fabric samples were comprehensively assessed. Analysis of the comprehensive assessment diagram and histogram of the fabric quality indicators showed that the quality indicators of the shirting fabric in variant IV are the best, being superior to the surfaces of other shirting fabrics; this fabric was produced with a weft density of 225 and a linear density of 20 tex, made from a blended fiber yarn with a 70/30 ratio.